Gas filtration through porous coal medium Effect of the gas constrained in micropores (Archives of Mechanics - Test, 1996)
Gas filtration through the macropores in porous coal media, with diffusion of a gas constrained in micropores, is investigated by using the homogenization process for periodic structures. This technique leads to the macroscopic model of the considered phenomenon by starting from the description at the pore level. No prerequisite is imposed at the macroscopic scale. Three different macroscopic models are obtained. Their ranges of validity are defined by appropriate dimensionless numbers that describe the geometrical structure and the physico-chemical properties of the coal. In two of these models, the micropore diffusion is coupled to the filtration process by a source term in the macroscopic mass balance. Finally, we investigate a one-dimensional flow through a semi-infinite coal seam, when the coal is assumed to be composed of grains. This simple example demonstrates the strong influence of the characteristic sizes of the grains and of the macroscopic sample on the filtration process.